54.3k views
4 votes
Choose the correct simplification of (2x3 + x2 − 4x) − (9x3 − 3x2).

11x3 − 2x2 − 4x
−7x3 + 4x2 − 4x
−2x3 − 2x2 − 4x
−7x3 − 4x2 − 4x

User Acfreitas
by
5.8k points

2 Answers

6 votes
2x^3 + x^2 - 4x - (9x^3 - 3x^2) =
2x^3 + x^2 - 4x - 9x^3 + 3x^2 =
-7x^3 + 4x^2 - 4x <===
User Headwinds
by
6.4k points
2 votes

Answer:

option (2) is correct.


(2x^3+x^2-4x)-(9x^3-3x^2)=-7x^3+4x^2-4x

Explanation:

Given expression
(2x^3+x^2-4x)-(9x^3-3x^2)

We have to choose the correct option that correctly simplify the given expression.

Consider the given expression
(2x^3+x^2-4x)-(9x^3-3x^2)

Opening the brackets , we get,

Applying plus-minus rule,
-(-a)=+a


(2x^3+x^2-4x)-(9x^3-3x^2)=2x^3+x^2-4x-9x^3+3x^2

LIKE TERMS are terms having same variable with same degree.

Adding like term , we get,


(2x^3+x^2-4x)-(9x^3-3x^2)=(2-9)x^3+(3+1)x^2-4x


(2x^3+x^2-4x)-(9x^3-3x^2)=-7x^3+4x^2-4x

Thus, option (2) is correct.

User Donparalias
by
5.6k points